Kaleidoskop der jungen DaF-/DaZ-Forschung Dokumentation zur zweiten Nachwuchstagung des Fachverbandes Deutsch als Fremdsprache - Peuschel, Kristina; Pietzuch, Jan P. (Universitätsverlag Göttingen, 2009)
The articles in this anthology display the diversity of innovative approaches chosen in ongoing or concluded PhD and professorial dissertations in the field of German as a Foreign or Second language. They include studies in text comprehension research, critical needs analysis, discourse analysis, empirical didactics and analyses of the learning process in its cultural context. In line with the characteristics of the kaleidoscope, the editors do without any systematic classification of the contributions and do not claim to establish some kind of carthography of the current state of young GFL/GSL reaearch. They would rather invite the reader to look optimistically on the development of young GFL/GSL research and reflect upon the structure and the instruments of support to young GFL/GSL researchers.